2012
DOI: 10.4097/kjae.2012.63.3.221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aprepitant for the prevention of postoperative nausea and vomiting in patients undergoing gynecologic surgery with intravenous patient controlled analgesia using fentanyl: aprepitant plus ramosetron vs ramosetron alone

Abstract: BackgroundThe purpose of this study was to evaluate the effect of an aprepitant, neurokinin-1(NK1) receptor antagonist, for reducing postoperative nausea and vomiting (PONV) for up to 24 hours in patients regarded as high risk undergoing gynecological surgery with intravenous patient-controlled analgesia (IV PCA) using fentanyl.MethodsIn this randomized, open label, case-control study 84 gynecological surgical patients receiving a standardized general anesthesia were investigated. Patients were randomly alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 24 publications
2
55
0
3
Order By: Relevance
“…The patients recruited in our study (aged 6-10 years old, undergoing strabismus surgery) are considered highly susceptible for PONV. In attempts to reduce the incidence PONV in patients with risk factors, multiple studies have shown that multimodal antiemetic therapies are more beneficial than a single approach [21,22]. Previous studies demonstrated that combined use of dexmedetomidine along with balanced anesthesia decreases the incidence of PONV in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The patients recruited in our study (aged 6-10 years old, undergoing strabismus surgery) are considered highly susceptible for PONV. In attempts to reduce the incidence PONV in patients with risk factors, multiple studies have shown that multimodal antiemetic therapies are more beneficial than a single approach [21,22]. Previous studies demonstrated that combined use of dexmedetomidine along with balanced anesthesia decreases the incidence of PONV in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aprepitant was also shown to be non-inferior to ondansetron for the first 24 h after surgery, and significantly more effective than ondansetron for preventing vomiting at 24 and 48 h after surgery (Diemunsch et al, 2007). Aprepitant has also been found to be effective when used in a multimodal approach to PONV prophylaxis, particularly with respect to prevention of vomiting (Habib et al, 2011; Lee et al, 2012; Vallejo et al, 2012). …”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…The most recent development in PONV pharmacology is aprepitant, a potent NK 1 antagonist that appears to work additively with other classes of antiemetics. There have been multiple studies demonstrating its efficacy in various patient populations (Diemunsch et al, 2007; Gan et al, 2007a; Habib et al, 2011; Lee et al, 2012; Vallejo et al, 2012), but further studies are required in order to potentially contribute to updating the guidelines for controlling PONV.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although our current trial's numbers failed to reach significance, there did appear to be a trend towards reduction of PONV in our study population. Three other studies from Korea and Japan [17]- [19] have had similar results in PONV prophylaxis using aprepitant preoperatively prior to gynecologic laparoscopy, but not specifically hysterectomy. These trials compared doses ranging from 80 -125 mg delivered orally 2 -3 hours prior to surgery versus placebo.…”
Section: Discussionmentioning
confidence: 79%